Awe Outlet / Tengku Muhammad Haris Muqriz Tengku Hisham - Tengku Hisham, Tengku Muhammad Haris Muqriz (2020)
For the study case for ent300 I was given the task to find a successful entrepreneur who produces his own product . I chose mohammad azwan bin mohammad aripin or awe because he is a native of Kelantan who was originally a Kelantan FA and Malaysian football player. However, he started trying the business world with his fiancé on a part-time basis only at first. He produced a shirt that not only has an interesting design but also a different shape from other clothes that feature a slightly longer back. Azwan started his business with a small capital but his longevity became an attraction because of the quality of his clothes and his more exclusive pattern. The majority of AWE.Outlet customers are natives, especially those who love football. The AWE.outlet brand is now successfully surviving in the business industry after constant demand.